High-temperature-resistant PC alloy for electronic tray and preparation method of high-temperature-resistant PC alloy
By using silazane and silane coupling agent in the PC alloy system to form a crosslinked structure, combined with saponified ethylene-vinyl acetate copolymer and nonionic surfactant, the existing PC-polyester alloys have been solved, and an alloy system with high heat resistance and impact resistance is achieved.
Patent Information
- Application Number
- CN202411811110.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-04
AI Technical Summary
The existing PC-polyester alloys have insufficient heat resistance and mechanical properties at high temperatures, and have poor compatibility after adding inorganic fillers, resulting in a decrease in tensile and impact resistance.
A grid-like crosslinking system is formed in the PC alloy system using silazane and silane coupling agent to improve heat resistance, and compatibility and uniformity are improved by adding saponified ethylene-vinyl acetate copolymer and nonionic surfactant.
The alloy's heat resistance and impact resistance are significantly improved, while maintaining good mechanical strength, avoiding compatibility problems when adding inorganic fillers.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of plastic products, and in particular to a high temperature resistant PC alloy for electronic trays and a preparation method thereof. Background Art
[0002] From personal consumer electronics to enterprise-level servers, automobiles, medical equipment and other industries, all rely on the application of chips. The domestic chip industry is developing rapidly, and its supporting electronic trays have a large demand and a good market prospect.
[0003] PC-polyester alloy is an available injection molding material for electronic trays. It has low-temperature brittleness resistance, chemical corrosion resistance and good rigidity. Since the chip needs to be baked before production to completely remove the moisture in the chip, the above material needs to have good heat resistance. Compared with other commonly used chip tray materials, such as polyether, PC-polyester needs to expand its heat resistance, and also needs to maintain good flatness, reduce internal cracks caused by injection molding, and improve uniformity. Summary of the invention
[0004] In order to provide a material that has high temperature resistance, good mechanical strength, no cracking during injection molding and good fluidity, the present application provides a PC alloy system.
[0005] First, the present application provides a PC alloy system, which comprises the following components in parts by mass:
[0006] PC-polyester composite material, 100 parts, of which PC resin accounts for 60-90 parts, and polyester can be PET or PBT;
[0007] Toughening agent, 2 to 8 parts;
[0008] Silane coupling agent: 0.5-1 part;
[0009] Nonionic antistatic agent, 1 to 5 parts;
[0010] Silazane, wherein the molar amount of the silazane is 0.1 to 0.2 times that of the silane coupling agent;
[0011] The PC alloy contains no inorganic filler, or contains inorganic filler accounting for no more than 5% of the total mass;
[0012] The PC alloy contains any number of antioxidants, anti-ultraviolet agents, antistatic agents, ester exchange inhibitors or lubricants in an amount not exceeding 10% of the total mass.
[0013] In the prior art, a commonly used method to improve the heat deformation temperature and heat resistance is to add a certain amount of inorganic filler to the system. The inorganic filler itself has rigidity, and most of the inorganic fillers are relatively stable when heated. Therefore, the heat deformation temperature of the system will be significantly improved, and the mechanical properties after long-term heating will also be improved to a certain extent. However, since the filler itself is an inorganic phase, its compatibility with the organic system is not good. In most cases, in order to improve the compatibility of the filler in the system, it must be treated with coupling components such as silane coupling agents to make the organic phase and inorganic phase compatible and evenly mixed. However, even so, the addition of fillers may still lead to a decrease in the tensile and impact resistance of the system.
[0014] In the above scheme, as a substitute for the filler system, silazane is selected and added to the system. Silazane itself is reactive and has multiple reaction sites. As a coupling center, it can form a grid-like cross-linking system, and the limiting effect of the grid-like system is used to improve the heat resistance, so that the impact resistance of the material after baking is not affected. At the same time, the central volume of silazane itself is small, so it is not easy to form a brittle structure in the system. Its overall tensile resistance and impact resistance are improved compared to the system with added fillers, forming an alloy system that is heat-resistant, impact-resistant and has strong mechanical properties as a whole.
[0015] Preferably, the silazane is a linear silazane, and further preferably, the silazane is H6DMS.
[0016] Compared with cyclic silazanes, linear silazanes have better reactivity and are not easy to form small-scale agglomerate structures in the system. Among them, H6DMS has active hydrogen on the central nitrogen atom, which can better participate in the formation of the central network system in the above system. Overall, it has better heat resistance, higher thermal softening temperature and better impact resistance.
[0017] Preferably, it also comprises 2 to 4 parts by weight of saponified ethylene-vinyl acetate copolymer. Further preferably, in the saponified ethylene-vinyl acetate copolymer, the molar percentages of ethylene monomer and vinyl alcohol monomer chain segments are 30 to 50% and 25 to 35%, respectively.
[0018] In the above scheme, the saponified ethylene-vinyl acetate copolymer system is added to hydrolyze part of the ester groups in the ethylene-vinyl acetate system to form an ethylene-vinyl alcohol-vinyl acetate ternary copolymer system. On the one hand, it can soften the system and reduce the processing temperature, so that the system has better uniformity and leveling performance, and the internal structure is more uniform. The vinyl alcohol structure can provide good reaction binding sites and hydrogen bonding performance, so that a more reliable cross-linking structure is formed in the system. After experiments, compared with the saponified ethylene-vinyl acetate copolymer system, the addition of polyolefins, polyvinyl alcohol, ethylene-vinyl alcohol copolymers or ethylene-vinyl acetate copolymers will have a certain adverse effect on the overall mechanical properties.
[0019] On the basis of the above, some components can be further added to improve the heat resistance and dispersion uniformity of the system. Since there are free hydroxyl groups in the saponified ethylene-vinyl acetate copolymer system, in the preferred embodiment, 1 to 5 parts by weight of non-ionic surfactant can be further added. Non-ionic surfactant can improve the compatibility of various items in the system without participating in the reaction, thereby improving the uniformity of the alloy.
[0020] Preferably, the invention further comprises 5 to 10 parts by weight of non-reactive silicone oil.
[0021] Non-reactive silicone oil refers to silicone oil that does not have active groups on silane, such as methyl silicone oil, methylethyl silicone oil, etc., while hydroxy silicone oil, hydrogen-containing silicone oil or vinyl silicone oil are not included. Adding non-reactive silicone oil to the system can adjust the composite system of silazane and coupling agent to be more evenly distributed in the above-mentioned plastic alloy system. At the same time, the silicon molecular chain also has better heat resistance, which allows the mechanical properties of the material to remain stable under long-term heating and is not prone to a significant decrease in impact strength.
[0022] In addition, the present application also relates to a method for preparing the above-mentioned high-temperature resistant PC alloy for electronic trays, wherein the raw materials are mixed and then extruded and granulated at 250-280° C. to obtain pellets, which are then injection molded.
[0023] In summary, the present application provides an alloy system of PC and polyester, which improves the heat resistance of the system by adding silazane and silane coupling agent into the system. On the one hand, it has a higher heat deformation temperature and good impact resistance. On the other hand, it can still maintain good mechanical properties after long-term high-temperature treatment. DETAILED DESCRIPTION
[0024] The technical solution of the present application is further described through the following specific implementation methods.
[0025] In this plan, some materials are selected as follows:
[0026] PC 1250Y resin (Jiaxing Teijin)
[0027] PET FG730 resin (Jiangsu Yizheng Chemical Fiber)
[0028] ASA toughening agent S-2001 (Mitsubishi, Japan)
[0029] PBT 1100 resin (China Bluestar)
[0030] Nonionic antistatic agent GMS (Heda)
[0031] Nonionic surfactant Tween 60
[0032] Silicone oils of different viscosities were purchased from Zhijiang Silicone.
[0033] ASA toughening agents can also be replaced by MBS toughening agents, such as MBS 701.
[0034] Saponified ethylene-vinyl acetate can be obtained by saponifying ethylene-vinyl acetate resin. Specifically, ethylene-vinyl acetate copolymer and sodium hydroxide (or other acid and base that can catalyze the reaction) are added to a toluene-alcohol system to obtain saponified ethylene-vinyl acetate resin. The saponification degree of the system can be controlled by the mass of the added sodium hydroxide, the reaction temperature and the reaction time. The reaction is carried out at a lower temperature and a lower alkali concentration as much as possible to reduce the breakage of the molecular chain.
[0035] The molar ratio of each monomer in the final saponified ethylene-vinyl acetate can be determined by titrating the sodium hydroxide in the residual solution. Since sodium hydroxide will participate in the reaction in equimolar amounts to generate sodium acetate during the reaction, the molar amount of sodium hydroxide participating in the reaction can be calculated by titrating with hydrochloric acid and phenolphthalein solution, and according to the initial molar amount of vinyl in the ethylene-vinyl acetate resin, the molar ratio of the vinyl monomer, vinyl alcohol monomer and vinyl acetate monomer in the saponified ethylene-vinyl acetate can be calculated.
[0036] The remaining additives are all commercially available conventional products.
[0037] The following embodiments all involve high temperature resistant PC alloys for electronic pallets. In each embodiment, the following method is used for preparation: after mixing the materials, they are extruded through a twin-screw extruder in the range of 250 to 280°C, and then the strips are water-cooled, air-dried, and granulated to obtain alloy pellets. The alloy pellets are baked at 140°C for 3 hours and then injection-molded into standard strips by an injection molding machine.
[0038] Among them, the extrusion temperature can be determined according to the fluidity of the actual slurry. The higher the temperature, the better the fluidity of the slurry. However, in fact, too high a temperature will cause the molecular chain to break, and the material is prone to glass transition, which will also cause the surface roughness to increase. In addition, too high a temperature will also lead to problems such as decreased weather resistance and mechanical properties of the system. Therefore, when it is controlled at 250-280°C as a whole, the processing performance and surface gloss can be better balanced. In actual processing, multiple experiments can be conducted to determine the optimal processing temperature.
[0039] In the following examples, the determination methods of various parameters are as follows:
[0040] Tensile strength: ISO527-2
[0041] Flexural modulus: ISO178
[0042] Izod notched impact strength: ISO180
[0043] Heat deformation temperature (0.45MPa): ISO 75-2.
[0044] The heat resistance of the system was tested by placing the system in an environment of 60°C and 70% humidity for 120 hours, cooling it to room temperature, and then measuring the tensile strength of the system.
[0045] For the thermal deformation resistance of the system, the sample was placed at 60°C for 12 hours, then at -20°C for 12 hours, alternately for a total of 120 hours, then returned to room temperature and the tensile strength of the system was measured. (Humidity was 70%)
[0046] It should be noted that since the above temperatures do not reach the thermal deformation temperature of the sample, let alone the glass transition temperature of the sample, it is reasonable to use them to measure the thermal weather resistance of the system.
[0047] Example 1: In this example, the amount and type of silazane in the system are mainly studied, wherein the silane coupling agent is fixed to HK-560, and the mass proportions of each component are as follows:
[0048] PC-PET composite system, including 75 parts of PC and 25 parts of PET;
[0049] 5 parts of toughening agent;
[0050] 0.5 parts of silane coupling agent;
[0051] 2 parts of nonionic antistatic agent;
[0052] 4 parts of saponified ethylene-vinyl acetate copolymer;
[0053] 3 parts of nonionic surfactant.
[0054] In addition, the following additives can also be added to the following schemes:
[0055] Transesterification inhibitor SAG 1.5
[0056] Silane coupling agent FD-5600.2
[0057] Antioxidant 1076 0.5
[0058] Lubricant PETS) 0.4
[0059] Ester exchange inhibitors, light stabilizers, UV inhibitors and antioxidants are all commonly used additives for plastic alloy systems. Their small addition will not have a significant effect on the performance of the system. Overall, the total amount added should not exceed 5% of the total plastic alloy system.
[0060] In this embodiment, a saponified ethylene-vinyl acetate copolymer obtained by saponifying an ethylene-vinyl acetate copolymer having a vinyl monomer content of 40% is used, and the saponification degree is about 55%, that is, the molar percentage of the vinyl alcohol monomer is 33%.
[0061] In the above system, the overall performance of PET alloy and PBT alloy is relatively close. In general, the amount of PET and PBT in the system can be adjusted according to the actual mechanical properties required, thereby obtaining PC-polyester alloys with different usage scenarios. The toughening agent can be any one of ASA toughening agent or MBS toughening agent. In this embodiment, ASA toughening agent is used as a representative, which can improve toughness and reduce rigidity as a whole. The amount can be adjusted within the range of 2 to 8 parts according to the actual product obtained.
[0062] In this embodiment, experiments were conducted with different amounts and types of silazanes, and the results are shown in Table 1.
[0063] Table 1
[0064]
[0065]
[0066] Through the above experiments, it can be seen that when the mass of silane coupling agent is fixed, increasing the mass of silazane will increase the overall thermal deformation temperature, and both the heat-resistant tensile strength and the temperature-resistant tensile strength will be enhanced, which proves that the PC alloy can still maintain good mechanical strength under long-term high temperature or alternating hot and cold conditions. However, if the amount of silazane added is too much, the heat resistance of the system will no longer be improved. Specifically, after the mass of silazane reaches a value close to that of the silane coupling agent, continuing to increase the amount of silazane has little effect on the heat resistance and temperature-resistant properties, and has a certain reduction in impact strength.
[0067] By comparison, among the four silazanes, the two cyclic silazanes have relatively little improvement in heat resistance and temperature change resistance in the system, which may be due to the smaller degree of crosslinking of the ring structure in the system. More specifically, H6DMS with active hydrogen on the central nitrogen atom will form a better heat resistance effect and better mechanical properties overall.
[0068] Example 2: Based on Example 1-2, the amount of silane coupling agent was adjusted according to the condition that the mass ratio of silane coupling agent to silazane was 1:1. The results are shown in Table 2.
[0069] Table 2
[0070]
[0071] According to the above data, the overall increase in the mass of silane coupling agent and silazane will make the system harder, the impact resistance will be stronger, the heat deformation temperature will increase, and the heat resistance and temperature change resistance will be stronger. The upper limit of the overall upward trend is when the mass of the silane coupling agent reaches 1 part. Continuing to increase it has no obvious effect on the heat resistance, but will cause a significant increase in the bending modulus. At the same time, there will be certain difficulties in the processing of the system. Therefore, the amount of silane coupling agent added should not be too much in actual processing.
[0072] Example 3: In this example, the molar ratio of the three monomers in the saponified ethylene-vinyl acetate copolymer is further adjusted. In this example, ethylene-vinyl acetate copolymers with four ethylene monomer contents are saponified to obtain different saponified ethylene-vinyl acetate copolymers, as follows:
[0073] A series, ethylene monomer content is 20%, specifically:
[0074] A-1: Vinyl alcohol monomer content 29%;
[0075] A-2: Vinyl alcohol monomer content 41%;
[0076] B series, ethylene monomer content is 30%, specifically:
[0077] B-1: Vinyl alcohol monomer content 22%;
[0078] B-2: Vinyl alcohol monomer content 35%;
[0079] B-3: Vinyl alcohol monomer content 57%;
[0080] C series, ethylene monomer content is 40%, specifically:
[0081] C-1: Vinyl alcohol monomer content 18%;
[0082] C-2: Vinyl alcohol monomer content 25%;
[0083] C-3: vinyl alcohol monomer content 33%; (i.e., the saponified ethylene-vinyl acetate copolymer used in Example 1)
[0084] C-4: Vinyl alcohol monomer content 45%;
[0085] D series, ethylene monomer content is 50%, specifically:
[0086] D-1: Vinyl alcohol monomer content 30%;
[0087] D-2: Vinyl alcohol monomer content 44%;
[0088] E: ethylene-vinyl alcohol copolymer, vinyl molar content 44%;
[0089] F: Ethylene-vinyl acetate copolymer, vinyl content 30% by molar amount.
[0090] The experimental results of adding different masses of different saponified ethylene-vinyl acetate copolymers are shown in Table 3.
[0091] Table 3
[0092]
[0093] Through the above experimental results, it can be seen that in the above system, whether ethylene vinyl alcohol or ethylene vinyl acetate is used, its strength increment to the system is smaller than that of partially saponified ethylene vinyl acetate copolymer. Among them, the vinyl segment is relatively soft as a whole, which improves the processing performance and processing uniformity of the system. At the same time, the higher the vinyl segment, the lower the bending modulus of the system, but the tensile strength and impact resistance will also be slightly reduced. When the vinyl content is 30-50%, that is, when saponified ethylene-vinyl acetate copolymers of Type B, Type C and Type D are used, the overall mechanical strength and heat resistance are the best. On the basis of the above, when the vinyl alcohol chain segment is controlled at 25-35%, the impact resistance and tensile strength are slightly higher than the structure outside the range. If the molar amount of vinyl alcohol is low and the molar amount of vinyl acetate is high, the tensile strength will be slightly lost. If the molar amount of vinyl alcohol is high and the molar amount of vinyl acetate is low, the impact resistance will be slightly reduced, and in the scheme with a higher vinyl alcohol content, the temperature change resistance will be greatly reduced. The possible reason is that in the scheme with a higher vinyl alcohol content, the internal moisture resistance is poor, and internal structural defects are more likely to occur under repeated high and low temperature conditions.
[0094] Example 4: In this example, non-reactive silicone oil is further added on the basis of Examples 1-2. Specifically, methyl silicone oil is selected in this example, and its five viscosity numbers are 300 mm 2 / s、500mm 2 / s、800mm 2 / s、1200mm 2 / s and 2500mm 2 / s.
[0095] Table 3
[0096]
[0097] From the above experiments, it can be seen that after adding non-reactive silicone oil in this solution, the heat resistance and impact resistance are improved to a certain extent, but the viscosity of the silicone oil needs to be at least 500mm 2 / s or above. In addition, excessive use of silicone oil will lead to a decrease in tensile strength, and when the viscosity of silicone oil is too high, it will also lead to a certain decrease in mechanical properties. The reason may be that the excessively long silicone oil molecular chain is easy to affect the uniformity of each component in the system, and thus easily form a clustered system.
[0098] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high temperature resistant PC alloy for electronic trays, characterized in that: The components are as follows according to mass parts: PC-polyester composite material, 100 parts, of which PC resin accounts for 60-90 parts, and polyester is PET or PBT; Toughening agent, 2 to 8 parts; Silane coupling agent: 0.1-1 part; Nonionic antistatic agent, 1 to 5 parts; Silazane, wherein the molar amount of the silazane is 0.5 to 0.1 times that of the silane coupling agent; The PC alloy contains no inorganic filler, or contains inorganic filler accounting for no more than 5% of the total mass; The PC alloy contains any number of antioxidants, anti-ultraviolet agents, antistatic agents, ester exchange inhibitors or lubricants in an amount not exceeding 10% of the total mass.
2. The high temperature resistant PC alloy for electronic tray according to claim 1, characterized in that: The silazane is a linear silazane.
3. The high temperature resistant PC alloy for electronic tray according to claim 2, characterized in that: The silazane is H6DMS.
4. The high temperature resistant PC alloy for electronic tray according to claim 1, characterized in that: It also includes 2 to 4 parts by weight of saponified ethylene-vinyl acetate copolymer.
5. The high temperature resistant PC alloy for electronic tray according to claim 4, characterized in that: In the saponified ethylene-vinyl acetate copolymer, the molar percentages of ethylene monomer and vinyl alcohol monomer chain segments are 30-50% and 25-35% respectively.
6. The high temperature resistant PC alloy for electronic tray according to claim 4, characterized in that: It also includes 1 to 5 parts by weight of a nonionic surfactant.
7. The high temperature resistant PC alloy for electronic tray according to claim 1, characterized in that: It also includes 5 to 10 parts by weight of non-reactive silicone oil.
8. The high temperature resistant PC alloy for electronic tray according to claim 7, characterized in that: The non-reactive silicone oil has a kinematic viscosity of 500 to 800 mm at 25°C. 2 / s.
9. The high temperature resistant PC alloy for electronic tray according to claim 1, characterized in that: The toughening agent is MBS toughening agent or ASA toughening agent.
10. A method for preparing a high temperature resistant PC alloy for an electronic tray according to any one of claims 1 to 9, characterized in that: The raw materials are mixed and then extruded and granulated at 250-280° C. to obtain pellets, which are then injection molded.